Implementation of Blended Learning Through Smartphone-Based Applications in Disaster in Nursing Courses - Yosi Oktarina; Nurhusna Nurhusna; M. A. Ade Saputra (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2018)
Introduction: Along with the development of technology, especially in the education world, blended learning method is one method that can be used by utilizing technology in the learning process. Blended learning methods with smartphone-based applications make it easy for students to access learning material and discuss directly, both with lecturers and classmates without having to face to face directly. The purpose of this study was to develop smartphone-based disaster in nursing learning applicationsand to determine the feasibility of disaster in nursing applications according to material experts, media experts, and student responses. Methods: This research design was research and development (R & D) designby adapting the development of ADDIE (analysis, design, development, implementation, and evaluation) models.Application validation was carried out on one material expert, one media expert, and ten students of the Nursing Study Program. The technique sampling used purposive sampling. Results: The results showed that based on the material experts, the application got score 92,5% (very feasible). Based on the assessment of media experts this application got score 93,75% (very feasible). Meanwhile, according to student's response this application got score >75% (very feasible). Conclussions: This application should be used in blended learning especially in disaster nursing course. Thus, the nursing student learning motivation and achievment can increase.